Bawaslu Pencegahan Kampanye Hitam: Mewujudkan Rumah Politik Sehat di Pemilu 2024: Bawaslu Black Campaign Prevention: Realizing a Healthy Political Home in the 2024 Election - Mirdad, Zunaida; Mardhiah, Nellis; Safrida, Safrida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The purpose of this service is to find out the role of Bawaslu in building healthy political home education in the 2024 elections. This is reviewed based on the theory of public bureaucratic ethics, including political values, administrative values, and shared values. The method of implementing community service activities used is participatory learning and action (PLA) by involving Bawaslu and the Village Youth Institution as empowerment targets who will later campaign for programs from the healthy political home in preventing black campaigns in Aceh, especially in the West Aceh region. The results of the activities that have been carried out show the role of Bawaslu and anti-black campaign policies in building a healthy political home in the 2024 Election through education and supervision, including: exploring cooperation with Bawaslu and village youth institutions, establishing education and information posts to improve healthy political literacy for the community and youth, establishing driving administrators, namely village youth, and socialization or training to form an understanding of the concept of healthy politics and preventing black campaigns in Aceh Barat has succeeded in realizing the Healthy Political House program as a preventive effort against black campaigns towards the 2024 elections.